Pollen morphology of members of southern African Boerhavia and Commicarpus (Nyctaginaceae) - Struwig, M.; Siebert, S.J.; Jordaan, A. (African Biodiversity & Conservation, 2013)
In southern Africa, Boerhavia L. and Commicarpus Standl. are the most species-rich genera of the Nyctaginaceae. Hitherto, the pollen morphology of only three southern African species of each of these genera has been described. A palynological study of the remaining species is therefore necessary to complete the information for the taxa. The pollen morphology of sixteen species was studied with light, scanning electron and transmission electron microscopy. Pollen grains of Boerhavia and Commicarpus are uniform in shape and sculpturing. Grains are spheroidal and pantoporate, and the tectum tubuliferous and spinulose. Pollen grains of the Boerhavia are 52–91 µm in diameter and those of Commicarpus 52–129 µm. Spinules in both genera are 1–5 µm long. Pore plates have one or two spinules. In both genera the exine is 3.5–11.5 µm thick, the tectum 0.9–3.9 µm thick and the collumellae 0.6–2.8 µm long. Foot layers are 0.9–5.1 µm thick and the endexine is barely visible. Size variation of the pollen grain, pore diameter and exine thickness overlap and cannot be used to distinguish between the two genera or the individual species.